2020
DOI: 10.17509/jsl.v3i3.22873
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship between Students’ Scientific Attitude and Students’ Learning Style in Junior High School

Abstract: The objectives of this study were to profile the relationship of scientific attitude level and learning style preference among junior high school students in Bandung. This study utilized a survey research design with a total sample size of 110 students. A scientific attitude questionnaire and a visual, auditory, and kinesthetic (VAK) learning style inventory were administered in this study. The questionnaire measures five aspects of scientific attitude, specifically rationality, curiosity, open-mindedness, ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Statistics is a science that studies how to collect, process, present, and analyze data and how to draw conclusions from survey results (Rasyad, 2003). In addition, descriptive statistics serve to reduce data to make it easier to interpret (Morissan, 2012). The data needed in this research were collected and obtained from SMPN 1 Muaro Jambi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics is a science that studies how to collect, process, present, and analyze data and how to draw conclusions from survey results (Rasyad, 2003). In addition, descriptive statistics serve to reduce data to make it easier to interpret (Morissan, 2012). The data needed in this research were collected and obtained from SMPN 1 Muaro Jambi.…”
Section: Methodsmentioning
confidence: 99%
“…Attitude is one of the important aspects and needs to be considered in the learning process (Jufrida et al, 2019;Kurniawati & Atmojo, 2017;Nugraha et al, 2020). The formation of the attitude of each individual becomes very important and becomes fundamental (Aithal & Aithal, 2019;Mauliza et al, 2021;Zaki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bhaskar reported that students' attitudes towards English learning affected their English performance [35]. Nugraha indicated that a close relationship could be observed between the scientific attitudes and learning style preferences of junior high school students in Bandung [36], Indonesia. Farooq believed that e-learning plays an effective role in the field of education [37].…”
Section: Hypothesis Proposalmentioning
confidence: 99%
“…Profil Sikap Ilmiah Peserta Didik.... produktivitas, pembangunan, dan nilai [10]. Pendapat dari Oloruntegbe & Omoifo menyatakan bahwa salah satu faktor yang dapat menyebabkan siswa memiliki orientasi sikap ilmiah yang buruk adalah kurangnya penilaian pada peserta didik [1]. Gambar 1.…”
Section: Tabel 4 Sikap Ilmiah Pada Peserta Didik Per Dimensiunclassified
“…Pendahuluan Fisika merupakan mata pelajaran yang bukan hanya tentang persamaan matematis atau rumus, melainkan harus memahami konsep yang ditemukan melalui peristiwa atau fenomena di sekitar kita yang kemudian dibuktikan melalui percobaan atau eksperimen. Menurut Ali Khan et al tiga tujuan utama pendidikan sains, yaitu: pengembangan ilmu pengetahuan (domain kognitif), keterampilan proses sains (domain motif psikis), dan sikap ilmiah (domain afektif) [1]. Pembelajaran fisika bertujuan memberikan bekal pengalaman dan keterampilan proses, meningkatkan kreativitas dan sikap Profil Sikap Ilmiah Peserta Didik.... ilmiah peserta didik [2].…”
unclassified